Experimental analysis on the effect of multi-level array hollow semi-stadium fins (HSSF) and baffles on solar thermal air collector - Afham Rahmat, Muhammad Aqil; Ibrahim, Adnan; Al-Aribe, Khaled M.; Syafiq Bin Mustaffa, Muhammad Ubaidah; Harmailil, Ihsan Okta; Ud Din, Sahibzada Imad (Elsevier Ltd, 2025)
An energy crisis is caused by the world's population expansion and growing energy consumption by global civilization, which encourages the usage of renewable energy technologies such as solar thermal collectors. Inefficient heat transmission lowers energy conversion and collector performance. This research aims to utilize a multi-level array of hollow semi-stadium fins (HSSF) with baffles to evaluate experimentally the double-pass solar air collector energy utilization. The proposed collectors with baffles and 1:2 and 1:4 multi-level spacing gaps are compared to the flat plate design at mass flow rates of 0.01-0.08 kg/s and irradiances of 400-800 W/m2. The experimental findings are verified with numerical and previously experimental studies. The findings indicated that the newly double-pass solar collector achieved a maximum thermal efficiency of 77.70 % at 800 W/m2, the highest useful energy of 934.83 Watts, and the highest enhancement efficiency of 30.67 %, indicating better performance than the flat plate design. Optimal efficiency was found at flow rates of 0.04 kg/s (400 W/m2) and 0.07 kg/s (600-800 W/m2). Increasing mass flow rates reduces friction factors while raising pressure drops. Validation with numerical results contains a 0.67-4.96 % error. Field-based experimental research, exergy and thermohydraulic studies, and economic and environmental studies are recommended to evaluate the design's effectiveness and feasibility.